Toward a cognitive science of markets: Economic agents as sense-makers - Samuel G. B. Johnson (Economics: The Open-Access, Open-Assessment E-Journal, 2019)
Behavioral economics aspires to replace the agents of neoclassical economics with living, breathing human beings. Here, the author argues that behavioral economics, like its neoclassical counterpart, often neglects the role of active sense-making that motivates and guides much human behavior. The author reviews what is known about the cognitive science of sense-making, describing three kinds of cognitive tools-hypothesis-inference heuristics, stories, and intuitive theories-that people use to structure and understand information. He illustrates how these ideas from cognitive science can illuminate puzzles in economics, such as decision under Knightian uncertainty, the dynamics of economic (in)stability, and the voters' preferences over economic policies. He concludes that cognitive science more broadly can enhance the explanatory and predictive quality of behavioral economic theories.
Keywords: A12; B4; D01; D11; D7; D8; D9; E7; G4; 330; cognitive science; behavioral economics; experimental economics; behavioral finance; economics methodology; information processing; decision-making under uncertainty